The distribution of private eye care service outlets in different districts in Selangor / Hadibah Naim Murad - Murad, Hadibah Naim (2015)
Background: A large number of studies concentrated in addressing the eye health workforce as the paramount in preventing the visual impairment and blindness globally leaving the eye health facility distribution especially in private sector remain neglected. The purpose of this thesis is to determine the distribution of private eye care service outlets in different districts in Selangor and the correlation exist between number of private eye care service outlets and the number of population. Methods: Data for the number of Selangor population was obtained from Department of Statistics Malaysia. Meanwhile, data for number of outlets in this study were obtained from Malaysian Optical Council (MOC), online search engine (Yellow Pages and Panpages) and Registration of Company (ROC) from Companies Commission of Malaysia (SSM). Data obtained then were sort accordingly where only private eye care practices were included in the study. Redundant data was checked by organizing the data according to alphabet and address of outlets. Results: Results showed a total of 1158 private eye care service outlet located in Selangor where 648 located in Petaling, 186 in Ulu Langat, 160 in Klang, 100 in Gombak, 32 in Kuala Langat, 12 in Kuala Selangor, 10 in Sabak Bernam, 7 in Sepang and 3 in Ulu Selangor. Descriptive statistical analysis using Spearman’s Correlation revealed a strong positive correlation exist between number of private eye care service outlet and the number of population, rs= 0.950, p < 0.01. Conclusion: The results demonstrated existence of maldistribution of private eye care service outlets where half of the total outlets were concentrated in high population district. A strong positive correlation between number of private eye care service outlet and number of population was noted. A more variable and extensive method during data collection was recommended to project the actual number of private eye care service outlets distributed across Selangor. The distribution inequities among different districts in Selangor may contribute to the lack of accessibility to eye and vision care in certain area of the region. Hence, a more comprehensive study should be done in order to minimize any unmet demand of eye services by the population.